Implying implausibility and undermining versus accepting peoples’ experiences of suicidal ideation and self-harm in Emergency Department psychosocial assessments - Bergen, Clara; Bortolotti, Lisa; Temple, Rachel Kimberley; Fadashe, Catherine; Lee, Carmen; Lim, Michele; McCabe, Rose (Frontiers in Psychiatry, 2023)
Background Patients seeking emergency care for self-harm and suicidality report varying experiences from being believed and taken seriously to not being believed and taken seriously. Epistemic injustice provides a conceptual framework to explore how peoples’ experiences of self-harm and suicidality are believed or not. We use an empirical method –conversation analysis – to analyze epistemics in clinical communication, focusing on how knowledge is claimed, contested and negotiated. In courtroom, police and political interaction, conversation analysis has identified communication practices implying implausibility in a person’s story to contest and recharacterize their accounts. Aims To investigate communication practices in Emergency Department (ED) biopsychosocial assessments that may (1) undermine, imply implausibility and recharacterize or (2) accept peoples’ experiences of suicidal ideation and self-harm. Methods Using conversation analysis, we micro-analyzed verbal and non-verbal communication in five video-recorded biopsychosocial assessments with people presenting to the ED with self-harm or suicidal ideation, and conducted supplementary analysis of participants’ medical records and post-visit interviews. We present three cases where experiences were not accepted and undermined/recharacterized and two cases where experiences were accepted and validated. Results When peoples’ experiences of suicidality and self-harm were not accepted or were undermined, questioners: did not acknowledge or accept the person’s account; asked questions that implied inconsistency or implausibility (“Didn’t you tell your GP that you were coping okay?”); juxtaposed contrasting information to undermine the person’s account (“You said you were coping okay before, and now you’re saying you feel suicidal”); asked questions asserting that, e.g., asking for help implied they were not intending to end their life (“So when you called 111 what were you expecting them to do”); and resistinged or directly questioned the person’s account. Multiple practices across the assessment built on each other to assert that the person was not suicidal, did not look or act like they were suicidal; that the person’s decision to attend the ED was not justified; that an overdose was impulsive and not intended to end life; asking why the person didn’t take a more harmful medication to overdose; that self-harming behaviors were not that serious and should be in the person’s control. Alternative characterizations were used to justify decisions not to provide further support or referrals to specialist services. At times, these practices were also delivered when speaking over the patient. When peoples’ experiences were accepted, practitioners acknowledged, accepted, validated suicidality/self-harm and introduced a shared understanding of experiences that patients found helpful. Non-verbal feedback such as nodding and eye contact was central in acceptance of patients’ accounts. Conclusion These findings advance our understanding of how peoples’ experiences of suicidality or self-harm are undermined or accepted in mental health encounters in the ED. They have important clinical implications: patients report that when their experiences are not accepted or undermined, this makes them more distressed, less hopeful about the future and discourages future help-seeking when in crisis. Conversely, acknowledging, accepting and validating suicidality/self-harm and introducing a new ways of understanding peoples’ experiences may make people less suicidal and more hopeful, generates shared understanding and encourages future help-seeking.